2015
DOI: 10.1038/bmt.2015.246
|View full text |Cite
|
Sign up to set email alerts
|

Geographic access to hematopoietic cell transplantation services in the United States

Abstract: The use of hematopoietic cell transplantation (HCT) has risen in recent years and additional increases are projected in the near-and long-term future. The complex nature of HCT, along with its potentially rigorous follow-up care requirements, presents numerous potential barriers to accessing this important service (for example, financial considerations, donor availability and sociodemographic factors). The distance between a patient and an HCT facility also appears to be an important factor in both HCT use and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Prior studies suggest that families travel significant distances (average 60–100 miles) for specialized pediatric care. 2123 We called all listed providers from the BCBS website that met our criteria. We did not restrict our search to providers listed as accepting new patients in order to maximize our sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies suggest that families travel significant distances (average 60–100 miles) for specialized pediatric care. 2123 We called all listed providers from the BCBS website that met our criteria. We did not restrict our search to providers listed as accepting new patients in order to maximize our sample size.…”
Section: Methodsmentioning
confidence: 99%
“…One small study examining access to stem cell transplantation in Canada found rural patients were somewhat less likely to receive an autologous HCT compared with urban patients, although this difference was not statistically significant, possibly due to small numbers [3]. A recent study found that the majority of Americans are located within reasonable driving distance of a stem cell transplantation center (78.6% within a 90-minute drive, 94.7% within a 180-minute drive) [4]. Although that study might suggest that physical geography is not a significant barrier to transplantation, it did not attempt to compare transplantation rates between rural and urban Americans, or to examine how transplantation rates vary by other sociodemographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell transplantation is a highly specialized treatment that is only available at a limited number of pediatric facilities in the United States 33 . Recent studies suggest that access to HCT may differ by race and SES, 34,35 a phenomenon at least partially driven by racial/ethnic differences in donor availability.…”
Section: Discussionmentioning
confidence: 99%